2019
DOI: 10.1016/j.engstruct.2019.109282
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue strength capacity of load-carrying fillet welds on ultra-high-strength steel plates subjected to out-of-plane bending

Abstract: Björk, Z. Barsoum (2019). Fatigue strength capacity of load-carrying fillet welds on ultra-high-strength steel plates subjected to out-of-plane bending, Engineering Structures, 196, 109282. The article has been published in its final form at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
(25 reference statements)
0
16
0
1
Order By: Relevance
“…where ΔF is the unit force range (force/length), a eff is the effective throat thickness, and Δσ m is the membrane stress at the plate component. In the prior investigation [22], fracture mechanics-based analysis showed that the weld root fatigue strength improvement gained by weld penetration refers to external throat thickness summed with weld penetration depth, p (see also dimensions shown in Fig. 2b) in the axially loaded cruciform joints.…”
Section: Axial Loadingmentioning
confidence: 94%
See 1 more Smart Citation
“…where ΔF is the unit force range (force/length), a eff is the effective throat thickness, and Δσ m is the membrane stress at the plate component. In the prior investigation [22], fracture mechanics-based analysis showed that the weld root fatigue strength improvement gained by weld penetration refers to external throat thickness summed with weld penetration depth, p (see also dimensions shown in Fig. 2b) in the axially loaded cruciform joints.…”
Section: Axial Loadingmentioning
confidence: 94%
“…Nevertheless, this model still lacks experimental validation, and this work aims to verify different models for assessing weld root failures using NWSs. In a previous work [22], an analytical method, different to the new model proposed in the final draft of the new revision of EC3, parts 1-9 [6], for calculating NWSs under bending loading, was proposed using the limited number of experimental fatigue test data. The results showed in accordance with the FAT36 design curve applied in association with the nominal stress approach.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the life for welded joints and components is dominated by fatigue crack growth. Further, it illustrates the reliability and popularity of fatigue strength and fatigue life assessments for different failure modes in welded joints (Zhang et al, 2018;Ahola et al, 2019a;Chapetti and Steimbreger, 2019;Liu et al, 2020). The contribution of either fatigue crack initiation or propagation onto the fatigue life is strongly influenced by the material properties and loading conditions.…”
Section: Introductionmentioning
confidence: 90%
“…The FRANC2D/L analysis was carried out in two stages with CASCA, which is a mesh generator with the capability to produce different types of mesh. In the second part, the boundary conditions, problem characteristics, stress analysis, input crack singularities, crack propagation, and the problem conclusion were determined [30,31]. In FRANC2D, the stress intensity factor was determined using the J-Integral method, which was calculated using the equivalent domain integral method, and the Energy Release Rate method, which was calculated using the crack-closing method.…”
Section: Franc2d/l Proceduresmentioning
confidence: 99%